2021
DOI: 10.1111/jgs.17055
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver support and place of death among older adults

Abstract: Background/objectives: As home becomes the most common place of death in the United States, information about caregiver support and place of death is critical to improve patient and caregiver experiences at end of life. We seek to examine (1) the association between family care availability and place of death; and (2) caregiving intensity associated with place of death. Design: 2017 National Health and Aging Trends Study and National Study of Caregiving; nationally representative cross-sectional study of decea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Bereaved people reported worse experiences in relation to hospital and care home deaths than deaths at home or hospice, as in pre-pandemic studies [25][26][27][28] . In the first ten weeks of the pandemic in the UK, deaths in care homes increased by 220%, and home and hospital deaths by 77% and 90%, respectively, while hospice deaths fell by 20% 29 .…”
Section: Discussionmentioning
confidence: 84%
“…Bereaved people reported worse experiences in relation to hospital and care home deaths than deaths at home or hospice, as in pre-pandemic studies [25][26][27][28] . In the first ten weeks of the pandemic in the UK, deaths in care homes increased by 220%, and home and hospital deaths by 77% and 90%, respectively, while hospice deaths fell by 20% 29 .…”
Section: Discussionmentioning
confidence: 84%
“…Bereaved people reported worse experiences of hospital and care home deaths than deaths at home or hospice, as in pre-pandemic studies. [26][27][28][29] Modelling of routine data from the first 10 weeks of the pandemic in the UK (7 March-15 May 2020), found deaths in care homes increased by 220%, and home and hospital deaths by 77% and 90% respectively, while hospice deaths fell by 20%. 30 The increase in home deaths was sustained 31 and hospices shifted their resources to the community.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The availability of family care resources included being married during the last year of life, number of children (0–3, 4–6, >6), and living with family members ( Choi et al, 2021 ; Gomes & Higginson, 2006 ; Lei et al, 2021 ). Deceased oldest-old with family members (i.e., spouse, children and their spouses, grandchildren and their spouses, and other family members) or friends as their primary caregivers during the last year of life were considered informal care groups.…”
Section: Methodsmentioning
confidence: 99%
“… Gomes & Higginson, 2006 ) and being married during their last year of life ( Cross, Ely, et al, 2020 ; Escobar Pinzon et al, 2011 ; Gisquet et al, 2016 ), were strongly associated with the likelihood of home death. One nationally representative study from the United States, which set the presence of a spouse, household size, and number of daughters and sons as indicators of potential family care availability, found that larger household size and more daughters could increase the likelihood of dying at home ( Lei et al, 2021 ). A recent cross-national study affirmed that family caregiving was positively associated with home death in the United States and European countries ( Ailshire et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation